Profitability, Leverage, and Company Size: A Comparative Analysis of Manufacturing Firm Value in Indonesia and Malaysia During COVID-19 - Utami, Wiwik; Nugroho, Lucky; Chairunesia, Wieta; Mulyani, Susi Dwi (Economics & Islamic Finance Journal (ECIF), 2024)
This study examines the influence of profitability (Return on Assets/ROA), leverage (Debt-to-Equity Ratio/DER), and company size (LNAssets) on company value (Tobin’s Q) in Indonesia and Malaysia during the COVID-19 pandemic. The research aims to compare these relationships in both countries, considering differences in market maturity and investor behavior. Employing a quantitative approach, the study uses secondary data from 50 manufacturing companies in Indonesia and 42 in Malaysia, covering 2019–2021. Multiple linear regression was applied to analyze the data. The findings reveal that ROA positively impacts company value in both countries, with a more substantial effect observed in Indonesia due to its less mature market environment. DER also positively influences company value, as moderate leverage signals financial stability and growth potential. However, LNAssets negatively affect company value in Indonesia, reflecting agency conflicts and operational inefficiencies, while its effect in Malaysia is insignificant, indicating better governance and asset management. The results highlight that market dynamics and investor sophistication shape the effect of financial metrics on company value. This study offers practical implications for investors and policymakers. It provides insights into interpreting financial signals across different market contexts for investors. For policymakers, it underscores the importance of enhancing corporate governance in Indonesia to mitigate agency conflicts. The study’s novelty lies in its comparative analysis of Indonesia and Malaysia, demonstrating how market maturity and governance structures influence the relationship between financial metrics and company value. These findings contribute to firm performance and valuation literature during economic disruptions.